2013
DOI: 10.1002/crat.201300201
|View full text |Cite
|
Sign up to set email alerts
|

Composition and morphological characteristics of sialoliths

Abstract: Sialolithiasis refers to pathological minerilazation in the salivary glands and ducts. Aiming to a better understanding of the formation phenomena, structural and morphological analysis of a relatively large ensemble of sialoliths extracted from 22 patients via sielendoscopy was performed. Characterization methods, including Fourier Transform Infrared (FTIR) Spectroscopy, X‐Ray Diffraction, Raman spectroscopy and Scanning Electron Microscopy (SEM), showed that the large majority of 90% of sialoliths were compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Teymoortash et al [18] analyzed sialoliths from Wharton's duct (a duct of the submandibular salivary gland) and discovered that the organic materials were predominantly concentrated in the outer shell of the stones and their components were glycoproteins, mucopolysaccharides, lipids, and cellular detritus (Phospholipids). Considerable research carried out by several groups such as Sabot et al in 2012 [19]; Szalma et al 2012 [20]; Faklaris et al 2013 [21]; and Kraaji et al 2014 [22]) have also advanced our understanding of stone architecture by showing that some can have a pure protein nucleus surrounded by mixed organic and carbonate apatite layers; whereas others can have internal layers of apatite covered by a dense and varnished crust of proteins and other organic compounds. In addition, Yiu et al [23] and Ho et al [24] recently reported that bone forming mechanisms involved in the early stages of kidney stone development and arterial calcification also require the participation of proteins and transcription factors.…”
Section: Protein Matrix Vs Organic Phase: Current Evidencementioning
confidence: 99%
“…Teymoortash et al [18] analyzed sialoliths from Wharton's duct (a duct of the submandibular salivary gland) and discovered that the organic materials were predominantly concentrated in the outer shell of the stones and their components were glycoproteins, mucopolysaccharides, lipids, and cellular detritus (Phospholipids). Considerable research carried out by several groups such as Sabot et al in 2012 [19]; Szalma et al 2012 [20]; Faklaris et al 2013 [21]; and Kraaji et al 2014 [22]) have also advanced our understanding of stone architecture by showing that some can have a pure protein nucleus surrounded by mixed organic and carbonate apatite layers; whereas others can have internal layers of apatite covered by a dense and varnished crust of proteins and other organic compounds. In addition, Yiu et al [23] and Ho et al [24] recently reported that bone forming mechanisms involved in the early stages of kidney stone development and arterial calcification also require the participation of proteins and transcription factors.…”
Section: Protein Matrix Vs Organic Phase: Current Evidencementioning
confidence: 99%
“…28 However, an analysis of mineral content would be of limited utility to determine the etiology, because metabolic acidosis would drive formation of calcium phosphate stones, 29 but more than 85% of sialoliths are composed of calcium phosphate in the general population. 28,30,31 Although the published data on the effects of inhibition of hCA have focused primarily on the kidney, the wide distribution of hCA in multiple organs would suggest that hCA-inhibiting drugs such as topiramate, acetazolamide, dorzolamide, and brinzolamide could have far-reaching effects. 1 It has been reported that at 60 days of topiramate treatment, 86% of patients have developed some level of hypocitraturia, 32 and studies have found correlations between topiramate use and bone and mineral metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Sialoliths show a single well-defined core constituted by material with low mineralization that support the nucleation hypothesis of an initial organic nidus 4 . The submandibular gland is the most affected organ (85%) and parotid and sublingual glands are affected in 10% and 5% of cases, respectively 5 . Recent studies show that while sialoliths have complex structure, with a central core surrounded by concentric layers, calculus and tonsilloliths do not present distinctive architecture 6 .…”
Section: Introductionmentioning
confidence: 99%